HUBUNGAN STRES, CEMAS, DAN DEPRESI DENGAN KEJADIAN MIGRAIN PADA MAHASISWA KEDOKTERAN DI JAKARTA - Safira Nurrezki; Robi Irawan (Bahasa Indonesia, 2020)
Introduction: Mental disorders such as stress, anxiety, and depression are becoming a global concern for young adults, especially among medical students. The tight schedule of medical education curriculum has shown to contribute to a high prevalence of mental disorders among students, which may increase the risk of physical symptoms such as migraines. Methods: Carried out at School of Medicine and Health Sciences Atma Jaya Catholic University of Indonesia - Jakarta, this cross-sectional study used a proportional sampling method. Depression, anxiety, and stress were measured by using DASS 42 scale and the incidence of migraine was measured by Migraine Screen Questionnaire (MS-Q). Data were statistically analyzed by using Chi-Square test with 95% significance level. Results: A total of 196 students had participated, consisting of 98 male and 98 female students, aged 18-21 years old, and they experienced stress (41.3%), anxiety (57.1%), and depression (26.5%). Migraine was found in (28.1%) of respondents with higher incidence among female students (61.8%). Stress, anxiety, and depression had a significant relationship with the incidence of migraines (p <0.01). Conclusion: Depression, anxiety, and stress are common among medical student in Atma Jaya Catholic University of Indonesia, and were significantly associated with the incidence of migraines. Further research is needed to describe other factors that can trigger migraines such as hormonal, physical, and dietary factors.